2020
DOI: 10.3390/ijerph17134648
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Cause Analysis of Cyberbullying in Korean Adolescents

Abstract: With the development of information and communication technology, online communication is becoming more active than offline meetings in daily life. This online communication is accelerating, especially as smartphone distribution and utilization become more prevalent. This communication in cyberspace has the advantage of people being able to communicate anytime, anywhere beyond time and place, while causing a variety of inappropriate consequences. A typical one is cyberbullying, which is a serious probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In our study, family support was found to have the strongest protective effect on cyberbullying involvement of all three types, and peer support contributed additionally to reducing the risk of cybervictimization. Other studies have proved the protective role of family only in victimization and the bullying-victimization [20,31,32,61]. The systematic review of dozens of longitudinal studies published between 2007 and 2017 confirmed that family and peer support, and attachment decrease the risk of becoming a bully and a bullyvictim, although the evidence on the causal relationships was scarce [62].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our study, family support was found to have the strongest protective effect on cyberbullying involvement of all three types, and peer support contributed additionally to reducing the risk of cybervictimization. Other studies have proved the protective role of family only in victimization and the bullying-victimization [20,31,32,61]. The systematic review of dozens of longitudinal studies published between 2007 and 2017 confirmed that family and peer support, and attachment decrease the risk of becoming a bully and a bullyvictim, although the evidence on the causal relationships was scarce [62].…”
Section: Discussionmentioning
confidence: 96%
“…This scale includes eight items, which are rated on a five-point scale from 0 (not at all) to 4 (very well). The item scores were summed with a score from 0 to 32 and categorized according to three levels: low (0-16), average (17)(18)(19)(20)(21)(22)(23)(24)(25) and high (26)(27)(28)(29)(30)(31)(32). The internal consistency of the scale was good (Cronbach's alpha = 0.842).…”
Section: Individual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to the statistics from [ 18 ], more than 85% of illegal filming contents are in the form of photographs making them convenient to take and store. The relatively high proportion of illegal photography means that digital sex crimes occur spontaneously rather than being planned, as in the case of cyberbullying [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital practices increase the risk of being exposed to cyber interpersonal violence (CIV) once everyone has access to the digital conversation, everywhere, with everyone. The use of digital tools confers numerous benefits to the social processes of adolescents; nevertheless, digital practices increase young people's exposure to interpersonal invasiveness, making them more susceptible to experiencing cyber dating abuse (CDA), cyberstalking, cyberbullying and sexting Jun 2020). According to recent studies, these forms of violence have received several labels, such as electronic abuse, online abuse, sexual abuse, online sexual abuse, cyber harassment (Flach and Deslandes 2017).…”
Section: Introductionmentioning
confidence: 99%